PUMACA: Pengembangan Media Puzzle Berbasis Matching Card pada Materi Bangun Datar Kelas IV di SD Muhammadiyah 5 Samarinda - Dea Agustina; Andi Asrafiani Arafah; Khusnul Khotimah; Muhlis Muhlis (FKIP Universitas Mataram, 2026)
Abstract This study aims to determine the development process, feasibility, student responses, and teacher responses to match card-based puzzle media in grade IV of elementary school. The research method used is Research and Development (R&D) with the ADDIE development model (analysis, design, development, implementation, evaluation). The research subjects were grade IV elementary school students. The instruments used were questionnaires from media experts, material experts, linguists, teacher responses, and student responses. The results of the feasibility validation by media experts showed that the instrument was declared very feasible with a percentage of 91%, material experts indicated that the instrument was declared very feasible with a percentage of 94%, linguists indicated that the instrument was declared very feasible with a percentage of 94%. The participant responses were divided into 2, namely small group trials and large group trials. The small group trial scored 91% while the large group trial scored 93%. Teacher responses showed that the resulting score was very good with a percentage of 96%. It was concluded that the match card-based puzzle media developed for grade IV of elementary school was feasible to be used in mathematics learning in schools.